Precise nutrition 2: Regression equations using KOH protein solubility to estimate digestible lysine and digestible arginine in commercial lots of soybean meal that have undergone overprocessing or auto combustion - Nelson Ruiz; Carl M. Parsons; Benjamin W. Parsons (Journal of Applied Poultry Research)
Summary: The objective of this study was to develop regression equations for lysine (Lys) and arginine (Arg) that would allow poultry nutritionists and formulators to estimate amino acid (AA) digestibility in commercial lots of solvent-extracted soybean meal (SBM) using a newly standardized protocol for KOH protein solubility (KOHPS). A total of 82 SBM samples, selected from 100 samples that were analyzed for in vivo AA digestibility, were analyzed for KOHPS. The KOHPS values ranged from 14 to 88 %, while digestible Lys coefficients ranged from 0.47 to 0.96. Digestible Arg coefficients ranged from 0.62 to 0.98. It became evident from total Lys and Arg analyses of the original samples that a net destruction of Lys and Arg occurred as KOHPS decreased; therefore, corrected digestibility coefficients were calculated using estimated total Lys and total Arg values. Estimated values were obtained utilizing regressions for each AA as a function of CP. Regressions on KOHPS were then run with and without corrected digestibility coefficients. Linear regressions provided the best fit for corrected digestible coefficients vs. KOHPS. The 1-slope broken line regression for Lys indicated that a plateau occurred at 80 % KOHPS and a digestible Lys coefficient of 0.88; therefore, an adequately processed solvent-extracted SBM should exhibit a minimum of 80 % KOHPS, which will yield an in vivo digestible Lys coefficient of 0.88. Equations developed from regression of digestible Lys and Arg coefficients against KOHPS herein will allow commercial poultry nutritionists and formulators to adjust AA digestibility in the formulation matrix for SBM according to its KOHPS.